ANALISIS SEKTOR UNGGULAN DAN POTENSI PENGEMBANGAN PUSAT PERTUMBUHAN PEREKONOMIAN DI KAWASAN STRATEGIS MALANG RAYA - Hindi Zahra Pragmadeanti; Farida Rahmawati (STKIP Persada Khatulistiwa Sintang, 2022)
The study aims to acquire the sectors featured in the city of Malang, Batu, and Malang regency which is included in the agglomeration area of Malang Raya, and the potential center growth economy in Malang. The data used in this study was the secondary data obtained from the Central Statistics Agency (BPS). The method analysis used in the study is LQ Analysis, Shift Share Analysis, Analysis of Klassen Typology, Overlay Analysis, Gravity Analysis, and the Williamson Index. The result showed that the city of Malang, Batu, and Malang regency has the same negative growth sector's procurement electricity and gas. Malang City is a potential area to become a Growth Center economy in the Malang Raya area because of its superiority comparative, a fast-growing area, and have a strong interaction with surrounding areas. Economics inequality in the Malang Raya area tends to increase every year started from 2018 to 2020